Pendekatan Komunikasi Islam Ayah dan Anak : Studi Pada Keluarga di Kecamatan Darussalam Banda Aceh - Ibnu Sa'dan (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
The purpose of this study is to look at the role of fathers in leading or building a family. Fathers have great duties and functions not only to earn a living but also as protectors, role models, educators. This understanding does not seem to be fully fulfilled by most people. Indonesia adheres to a patriarchal system, thus seeing the father's role as only earning a living for his family. As a result, the father's role becomes partial and creates an imbalance in forming a family. Many children lose a father figure physically and psychologically, making children look for happiness, story friends other than their family. By building Islamic communication, it is hoped that the father's presence can be felt by children and families. The research method used is descriptive analytical method with qualitative approach. The data collection method is by conducting interviews with a number of fathers who live in Darussalam District, Banda Aceh. The results showed that to form a harmonious family, knowledge and religious knowledge are needed by applying Islamic communication principles such as qaulan karima, qaulan baligha, qaulan maysura, qaula sadida, qaulan layyina, qaulan ma'rufa. And it must be balanced by maximising the role of the father to be a family economic supporter (economic provider), providing time for the family (friend and playmate), providing a sense of comfort (caraviger and protector).